2011
DOI: 10.1590/s1517-83822011000300022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chitinase with antifungal activity from a native Serratia marcescens B4A

Abstract: Chitinases have the ability of chitin digestion that constitutes a main compound of the cell wall in many of the phytopathogens such as fungi. In the following investigation, a novel chitinase with antifungal activity was characterized from a native Serratia marcescens B4A. Partially purified enzyme had an apparent molecular mass of 54 kDa. It indicated an optimum activity in pH 5 at 45ºC. Enzyme was stable in 55ºC for 20 min and at a pH range of 3-9 for 90 min at 25ºC. When the temperature was raised to 60ºC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 32 publications
3
66
0
2
Order By: Relevance
“…Chitinase activity at temperature 20°C was only found on S. marcescens KAHN 15.12 although, it was lower than the optimum temperature. The same result also reported that chitinase had optimum activity between 35-75°C (Wang et al, 2002;Dai et al, 2011;Tu et al, 2010;Zarei et al, 2011;Asril et al, 2014;Laribi-Habchi et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Chitinase activity at temperature 20°C was only found on S. marcescens KAHN 15.12 although, it was lower than the optimum temperature. The same result also reported that chitinase had optimum activity between 35-75°C (Wang et al, 2002;Dai et al, 2011;Tu et al, 2010;Zarei et al, 2011;Asril et al, 2014;Laribi-Habchi et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…This occurred because of S. marcescens KAHN 15.12 had a chitinase specific activity that was higher than B. amyloliquefaciens SAHA 12.07, it was alleged the ability to lyse G. boninense cell wall will be higher and NAG will be produced in the higher number. This is supported that Serratia marcescens has also known as a potential chitinase producing bacteria that has been widely applied as biocontrol (Tu et al, 2010;Zarei et al, 2011;Okay et al, 2013;Fadhil et al, 2014). In the condition above optimum time, here concentration of NAG decreased.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This conclusion was also reported in previous studies of other strains of Serratia sp. (Parani et al, 2011;Zarei et al, 2011) …”
Section: Effect Of Initial Phmentioning
confidence: 99%
“…Purified antifungal proteins from different Serratia sp. strains have different molecular weights that range from 47 to 62 kDa (Roberts and Cabib, 1982;Frankowski et al, 2001;Kamens et al, 2003;Zarei et al, 2011;Babashpour et al, 2012;Fadhil et al, 2014). The final yield of the purification procedure was 28% (Table 2).…”
Section: Purification and Identification Of Antifungal Proteinmentioning
confidence: 99%